Inland Navigation Contributes to the Remobilization of Land-Based Plastics Into Riverine Systems - Climo, Joshua D.; Oswald, Stephanie B.; Buschman, Frans A.; Hendriks, A. Jan; Collas, Frank P. L. (Frontiers in Water, 2022)
Riverine systems are directly affected by plastic pollution and function as pathways for plastic transport to the sea. Plastic litter can enter the water by remobilization from the bed or from the riverbank, after which it can be transported with the flow. The process of remobilization is still poorly understood. To get a detailed understanding of the role rivers play in plastic transport and hence develop management measures to prevent or mitigate plastic transport it is vital to get a fundamental understanding of the factors contributing to remobilization of plastic on the riverbank. Therefore, we investigated how the wave action of inland navigation, one of the dominant actors in anthropogenic rivers, affects the remobilization of land-based plastics. Quantification of remobilization was performed along the riverbank of an intensely navigated river in the Netherlands (the river Waal) allowing for a real-world assessment of remobilization. Plastic pieces were placed at standardized distances from the average waterline to determine the plastic remobilization along the riverbank at different locations. Subsequently, wave actions of passing inland navigation was used to assess plastic remobilization. Inland navigation induced wave action was found to significantly cause remobilization of plastics present on the riverbank. The distance of the plastic object to the waterline combined with the wave height, riverbank slope and plastic size significantly affected remobilization probability. Overall, the remobilization effect was strongest on plastics present within ≤ 1.0m from the waterline. With a wave height ≥ 0.5m all plastics present up to 3.0 m from the waterline were remobilized and thereby potentially transported downstream through the river.